A SURVEY ON CHINESE COLLEGE STUDENTS ATTITUDES TOWARDS SPOKEN ENGLISH PROFICIENCY - Pan Bingxin; Fu Xiaoli (Celt: A Journal of Culture, English Language Teaching & Literature, 2005)
Based on the results of fieldwork research, this article attempts to explore the relation between college students standard of spoken English and their oral English level in Chinese context. It has been found that most of the students have set unrealistic goals toward the proficiency of spoken English, which in turn hampers their initiative to participate in oral activities in and out of classroom setting. There are many possible explanations of this phenomenon, namely, the mistakenly assumed status of English, the different expectations of the English utterances in terms of linguistic accuracy on the part of speakers and listeners, and the unique Chinese conservative characters. Suggestions on countermeasures especially those that might be conducted in class are presented at the end of the article.